KNOWLEDGE, ATTITUDE AND PRACTICE OF UNSAFE ABORTION AMONG IN-SCHOOL ADOLESCENTS IN OYO WEST LOCAL GOVERNMENT AREA - Ehondor, Esohe; Obisesan, Olubunmi; John, Gift; Uye, Emmanuel (Jurnal Saintifik (Multi Science Journal), 2025)
Abortion is one of the leading causes of maternal mortality especially in developing countries where crude methods are frequently used. Studies on the level of knowledge, attitude and practice of unsafe abortion among in-school adolescents are sketchy. This study was conducted to fill these gaps in knowledge. Cross-sectional survey design was adopted while simple random sampling technique was used to select five secondary schools in Oyo West Local Government Area. Data were collected from 200 female participants using validated questionnaires and analyzed with descriptive and Chi-square (χ2) statistics to answer three research questions and test two hypotheses, respectively. The result revealed that 83% of in-school adolescents had good knowledge of abortion, 80% had a positive attitude toward abortion, while 65% indicated that they had carried out abortion. Furthermore, the result revealed that attitude significantly influenced the practice of unsafe abortion (χ2 = 30.307, p < 0.05), while age did not (χ2 = 4.830, p > 0.05). The study concluded that female in-school adolescents (13-19) age bracket had good knowledge and positive attitude toward abortion and had practiced abortion more than once. The study recommended effective counseling and targeted health campaigns on the danger of engaging in unsafe abortion among in-school adolescents.